Truth-Seeking Judgment Aggregation over Interconnected Issues - Irem Bozbay (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper analyses the problem of aggregating judgments over multiple interconnected issues. We enrich the model by introducing the private information underlying individuals' judgments. Individuals share a common preference for reaching true collective judgments, but hold private information about what the truth might be. Information conflicts may occur both between and within individuals. Assuming strategic voting in a Bayesian voting game setting, we determine the voting rules which lead to collective judgments that efficiently incorporate all private information. We characterize the (rare) situations in which such rules exist, as well as the nature of these rules.
Keywords: D70; D71; 330; judgment aggregation; private information; efficient information aggregation; strategic voting